Biology and Management of Garden Spurge (Euphorbia hirta) in Ornamental Crop Production - Thomas Smith; Chris Marble; Shawn Steed; Nathan Boyd (EDIS)
Garden spurge is a prostrate (low-growing), herbaceous, short-lived, warm-season annual weed commonly found growing in Florida landscapes, container nurseries, and other agricultural production areas. This article is written for green industry professionals and others to aid in the identification and management of garden spurge in and around ornamental plants.